Mobility patterns consideration of educational facilities distribution model formulation in Southeast Malang Regional development plan - Respati Wikantiyoso; Tonny Suhartono; Pindo Tutuko; Aditya Galih Sulaksono (ARTEKS : Jurnal Teknik Arsitektur, 2022)
Regional disparities, and urban sprawl, will cause inequality in mobility between regions—one of the causes of the uneven distribution of educational facilities. The study of mobility patterns provides an overview of student movement patterns from and to school. The analysis is needed to determine the potential problems due to spatial disparities in the settlement Development Area. The research purpose; is (1) to obtain a model for determining the location and distribution of public schools based on mobility patterns in urban settlement development areas and (2) to obtain the model formulation for spatial planning distribution of educational facilities. This research uses a descriptive exploratory method with Space Syntax analysis. The research location was selected using the Classified Purposive Sampling method with an observation scale in the Development Area. The school zoning system has implications for equal distribution of education, reducing the mobility gap between regions, reducing congestion, air pollution, and dependence on motorized transportation. The study results of patterns of connectivity, accessibility, and mobility become a consideration for the placement of educational facilities in the Development Area. This study will improve the arrangement of spatial patterns and distribution of educational facilities based on studies of connectivity, regional accessibility, and student mobility.